Social structure, space and possession in Tongan culture and language : an ethnolinguistic study - Völkel, Svenja (Culture and language use, 2010)
This interdisciplinary study investigates the relationship between culture, language and cognition based on the aspects of social structure, space and possession in Tonga, Polynesia. Grounded on extensive field research, Völkel explores the subject from an anthropological as well as from a linguistic perspective. The book provides new insights into the language of respect, an honorific system which is deeply anchored in the societal hierarchy, spatial descriptions that are determined by socio-cultural and geocentric parameters, kinship terminology and possessive categories that perfectly expre.